Helicobacter pylori : importância dos genes da ilha e de adesão no câncer gástrico (Intestinal e Difuso) e em estudos de risco - Pereira, Eliane dos Santos (2015)
Gastric cancer (GC) is the third cause of cancer death worldwide. The etiology of gastric cancer is multifactorial and it i s being well established an association with infection by Helicobacter pylori . The genetic susceptibility to GC is postulated by exposure of a large proportion of the population to risk factors, but only part of this people develops the neoplasia. Furtherm ore, the H. pylori pathogenic character is given by the presence of cag - PAI pathogenicity island (cytotoxin associated gene pathogenicity island - cagPAI ) as well as allelic variation vacA s1m1 . About the host, genetic polymorphisms have been associated wi th the risk of GC, indicating these changes are potential genetic susceptibility markers in these tumors, however, few repair enzymes SNPs are studied. In the context of gastric carcinogenesis, it is necessary to consider the differences about histopatholo gy, age and gender. So, the aim of this study is to investigate the association of SNPs in DNA repair genes, APE1 2197 (T> G) and MLH1 - 93 (G>A), added to CDH1 - 160 (C>A) and - 347 (G>GA) SNPs. The CDH1 protein is associated with hereditary diffuse cancer an d genetic susceptibility. The histological subtypes, age and sex were importante data considered to the analyses. H. pylori genotype was determined by the presence of genes. cagA , cagE, cagG, cagT, virB11, vacA, oipA and hopQII. The H. pylori genotypes con sidered at risk study and individualized in the latest study. For this, it were included 285 patients with gastric cancer and 391 healthy controls matched for age and sex (1: 1 or 1: 2) from two different regions in Brazil: Ceará and Pará. The positivity f or H. pylori was observed in 87.71% of cases. In a risk study was observed a protection for intestinal tumors and it was associated with the G allele of APE1 (T> G) in women <55 years and GA allele CDH1 - 347 (G>GA) for men aged ≥ 55 years. In diffuse tumors, the group aged <55, the A allele of MLH1 - 93 (G>A) was associated with protection and the G allele of APE1 (T>G) was associated with risk in men in this age group. The G allele of APE1 (T>G) was also associated with the absence of distant metastases and the A allele of MLH1 (G>A) with absence of lymph nodes commitment. In the intestinal subtype, carriers patients G allele of APE1 (T>G were infected with significantly less virulent strains. In the stu dy with H. pylori strains, most cases had the full island regardless of histologic subtype. The cagA and cagE genes were present in most strains. According to the classification tree method analysis, some genes as cagG and cagE (in vacAs1 strains) proved f undamental in the separation of GC histological subtypes. The presence of cagG and cagE genes concomitantly or absence of cagG in H. pylori looks like classifies the intestinal tumor. While the presence of the cagG gene associated with the cagE absence cla ssifies the diffuse tumors. The cagM (+) cagG (+) genotype with the presence of the cagE gene classifies the intestinal tumor, since in the absence of cagE the tumors are classified by diffuse type. Regarding adhesion genes, there was a greater frequency o f oipA gene, followed by hopQI and hopQII . In summary, these data indicate that H. pylori genotype, histological subtype tumors, age and gender are important factors to be considered in polymorphisms analyzes. Despite the complexity to explain what are the factors that contribute to the separation of strains in intestinal and diffuse subtypes, it is clear that there are different pathways associated with these strains. And these genes may be potential markers of different histological subtypes.